The Nexus among Unemployment, Economic Growth and Crime: New Evidence from Nine South African Provinces - Shylet, Masunda (International Journal of Economics and Financial Issues, 2025)
This study investigated the long-run impact of key economic factors—including general unemployment, disaggregated youth and adult unemployment, economic growth (GDP), the Food Poverty Line (FPL), and disposable income—on crime rates across South Africa’s nine provinces. Utilising the 2002-2022 panel datasets, a Fully Modified Ordinary Least Squares (FMOLS) model was employed to estimate these long-run equilibrium relationships. The findings revealed a consistent and statistically significant positive long-run relationship among all forms of unemployment and crime, with adult unemployment showing a more pronounced impact. The FPL also consistently exhibited a positive and reliable link to higher crime. Conversely, disposable income demonstrated a robust inverse relationship with crime, indicating that increased income reliably reduces criminal activity. The relationship between economic growth (GDP) and crime was mixed and varied, reflecting the complexity observed in broader literature. These results resolve part of the mixed empirical evidence dilemma by highlighting significant provincial heterogeneity, underscoring that crime in South Africa is deeply embedded in local socio-economic structures and historical legacies, thus enriching the understanding of economic models of crime and Strain Theory. The study recommends abandoning uniform national crime prevention strategies, favouring localised, evidence-based approaches. Policy must prioritise and aggressively target job creation, particularly for adults, given their pronounced impact on crime rates.